Does Phospholipase Have a Role in Killing and Sodium Dodecyl Sulfate Lysis of T4 Ghost-Infected Escherichia coli? - Vander Maten, M. (1974)
The activation of Escherichia coli phospholipase by T4 ghost attachment was shown not to have a significant role in the killing or in the increased sensitivity of the bacterial cells to lysis by sodium dodecyl sulfate.